2022
DOI: 10.3390/jpm12020296
|View full text |Cite
|
Sign up to set email alerts
|

Electron Microscopy Reveals Evidence of Perinuclear Clustering of Mitochondria in Cardiac Biopsy-Proven Allograft Rejection

Abstract: Acute cellular rejection is a major complication in heart transplantation. We focus on the analysis of new ultrastructural findings in cardiac biopsy rejection based on mitochondrial intracellular organization. This study includes heart transplanted patients from a single center who were referred for endomyocardial biopsies as a scheduled routine screening. Participants were divided into two groups: patients transplanted without allograft rejection (Grade 0R), and patients with biopsy-proven allograft rejectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Previous studies have reported alterations in calcium metabolism in patients with cellular rejection and primary graft dysfunction, with lower levels of Serca2a in patients who present these complications after HT [ 5 , 20 ]. In addition, perinuclear changes have been observed in biopsies of patients with cellular rejection [ 21 ]. Furthermore, ACR episodes have been associated with elevated levels of circulating troponin [ 6 ], and especially B-type natriuretic peptide, in addition to NT-proBNP [ 6 , 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported alterations in calcium metabolism in patients with cellular rejection and primary graft dysfunction, with lower levels of Serca2a in patients who present these complications after HT [ 5 , 20 ]. In addition, perinuclear changes have been observed in biopsies of patients with cellular rejection [ 21 ]. Furthermore, ACR episodes have been associated with elevated levels of circulating troponin [ 6 ], and especially B-type natriuretic peptide, in addition to NT-proBNP [ 6 , 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%